2010
DOI: 10.1007/s11239-010-0471-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response to percutaneous coronary intervention in stable coronary artery disease

Abstract: Percutaneous coronary intervention (PCI) can be regarded as a model for mechanical induced plaque rupture. The objective of this study was to evaluate the inflammatory response to PCI in stable coronary artery disease (CAD) by analysing plasma levels of a wide range of inflammatory mediators. Consecutively, we included 36 patients with stable angina pectoris after successful revascularization by PCI with implantation of a bare metal stent (BMS) or a drug eluting stent (DES). Patients were followed for 7 days w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
1
14
0
5
Order By: Relevance
“…The results support mfa-1-dependent secretion of MMP-9 by mDCs (Figure 3D). Other indicators of risk of plaque rupture, including C1q (49), HSP60/HSP70 (reviewed in (50), CCR2 (51) and CXCL16 (52) (53) were analyzed at the mRNA level (Figure 3E). Analysis of these transcripts indicates that C1q, HSP60, HSP-70, CCR2 and CXCL16 are upregulated in response to fimbriated Pg381, relative to untreated control.…”
Section: Resultsmentioning
confidence: 99%
“…The results support mfa-1-dependent secretion of MMP-9 by mDCs (Figure 3D). Other indicators of risk of plaque rupture, including C1q (49), HSP60/HSP70 (reviewed in (50), CCR2 (51) and CXCL16 (52) (53) were analyzed at the mRNA level (Figure 3E). Analysis of these transcripts indicates that C1q, HSP60, HSP-70, CCR2 and CXCL16 are upregulated in response to fimbriated Pg381, relative to untreated control.…”
Section: Resultsmentioning
confidence: 99%
“…Kotooka et al [ 17 ] reported that the plasma PTX3 levels began to increase at 15 min after coronary stenting and reached a maximum at 24 h in the coronary sinus and peripheral blood. Other 2 studies also found PCI could mediate the increase of PTX3 [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 97%
“…This is followed by a statistically significant (P < 0.05) increase in the levels of sCD40 ligand from the pre-PCI time line to follow-up. An increase in sCD40L 7 days after PCI of stable coronary artery disease patients has recently been reported [5].…”
mentioning
confidence: 94%